Review of Policy-Oriented Research on Maternal Mortality - Komalasari, Dewi; Daniels, Jane (Yayasan Jurnal Perempuan, 2019)
Maternal mortality remains an unresolved critical issue. This condition indicates that women’s reproductive health rights has not yet been fulfilled. Maternal mortality occurs due to medical and non-medical factors. Even though a small amount of those deaths still happens due to unpreventable causes, however, most of those deaths could have been prevented and avoided. Government efforts to address the problem of maternal mortality are carried out through various policies that focus on medical factors and through programs aimed at increasing the coverage and quality of maternal health services. On the other hand, other factors such as social economic and cultural are being neglected. A review of researches on the theme of maternal mortality found various factors that contributed to the causes of maternal mortality such as socio-cultural barriers that limit women’s access to health, ranging from poverty, geography and local culture. Unmet need for contraception in family planning program, adolescence reproductive health issue that still hasn’t been addressed in a serious and comprehensive manner, as well as unsafe abortion are the key underlying causes of maternal mortality.